Oxytocin pathways in the intergenerational transmission of maternal early life stress. (February 2017) - Toepfer, Philipp; Heim, Christine; Entringer, Sonja; Binder, Elisabeth; Wadhwa, Pathik; Buss, Claudia
Highlights: Oxytocin plays a role in the intergenerational transmission of early adversity. Putative pre- and postnatal OT pathways of transmission are proposed. Oxytocin receptor gene ( OXTR ) variants affect susceptibility to the environment. The role of OXTR DNA methylation is discussed as a mechanism of transmission. Critical assessment of methodological challenges in human OT research is provided. Abstract: Severe stress in early life, such as childhood abuse and neglect, constitutes a major risk factor in the etiology of psychiatric disorders and somatic diseases. Importantly, these long-term effects may impact the next generation. The intergenerational transmission of maternal early life stress (ELS) may occur via pre-and postnatal pathways, such as alterations in maternal-fetal-placental stress physiology, maternal depression during pregnancy and postpartum, as well as impaired mother-offspring interactions. The neuropeptide oxytocin (OT) has gained considerable attention for its role in modulating all of these assumed transmission pathways. Moreover, central and peripheral OT signaling pathways are highly sensitive to environmental exposures and may be compromised by ELS with implications for these putative transmission mechanisms. Together, these data suggest that OT pathways play an important role in the intergenerational transmission of maternal ELS in humans. By integrating recent studies on gene-environment interactions and epigenetic modifications in OT pathway genes, the present review aims to develop a conceptual framework of intergenerational transmission of maternal ELS that emphasizes the role of OT.